Repression of the iron exporter ferroportin may contribute to hepatocyte iron overload in individuals with type 2 diabetes - Qiu, Ruiyue; Alikhanyan, Kristina; Volk, Nadine; Marques, Oriana; Mertens, Christina; Ruban Agarvas, Anand; Singh, Sanjana; Pepperkok, Rainer; Altamura, Sandro; Muckenthaler, Martina (Molecular metabolism, 2022)
Hyperferremia and hyperferritinemia are observed in patients and disease models of type 2 diabetes mellitus (T2DM). Likewise, patients with genetic iron overload diseases develop diabetes, suggesting a tight link between iron metabolism and diabetes. The liver controls systemic iron homeostasis and is a central organ for T2DM. Here, we investigate how the control of iron metabolism in hepatocytes is affected by T2DM.
Gesehen am 15.11.2023